Knowledge, attitude, and practice toward tuberculosis prevention and management among household contacts in Suzhou Hospital, Jiangsu province, China - Zhang, Yuping; Wu, Jingwen; Hui, Xiaoyan; Zhang, Peipei; Xue, Fang (Frontiers in Public Health, 2024)
Background China is among the 10 high-burden tuberculosis (TB) countries in the world; thus, investigation and management of household contacts is an essential part of TB prevention strategy. Objective To explore the knowledge, attitude, and practice (KAP) toward TB prevention and management among household contacts of TB patients. Methods This cross-sectional study enrolled household contacts in Suzhou Hospital of Integrated Traditional Chinese and Western Medicine between September 2022 and January 2023; KAP and demographic characteristics were assessed with the self-designed questionnaire and analyzed by multivariate logistic regression. Results A total of 503 participants were included; of them, 280 (55.78%) were female, and 303, (60.36%) aged ≥45 years. The KAP scores were 6.24 ± 2.20 (possible range: 0–12), 18.69 ± 2.80 (possible range: 0–36), and 20.37 ± 5.15 (possible range: 0–36), respectively. Suburban (OR = 0.18, 95% CI: 0.04–0.79, p = 0.023) and rural (OR = 0.12, 95% CI: 0.03–0.57, p = 0.008) were independently associated with knowledge. Positive attitude (OR = 7.03, 95% CI: 2.92–16.96, p < 0.001), education (high school or technical secondary school, OR = 4.91, 95% CI: 1.63–14.73, p = 0.005; college and above, OR = 14.94, 95% CI: 3.51–63.58, p < 0.001), and shorter disease duration (3–6 months, OR = 0.40, 95% CI: 0.18–0.90, p = 0.026) were independently associated with better practice scores. Conclusion Household contacts of TB patients demonstrated insufficient knowledge, unfavorable attitude, and suboptimal practice toward TB prevention and management. Tailored interventions are needed to ensure information accessibility, especially for individuals living in suburban and rural areas.